ANALYSE DU BUDGET D’EXPLOITATION ET SON INCIDENCE SUR LA GESTION D’UN ETABLISSEMENT SCOLAIRE : Cas du Complexe Scolaire TUUNGANE de 2018 à 2020 - KASIMU, GOMES YAHAYA; Pierre, UTCHINGA WELA (IJRDO - Journal of Business Management, 2022)
The major concern that prompted us to carry out this research is to analyze the operating budgets of the Tuungane School Complex in order to identify its impact on management.  Taking this concern into account, we formulated the following question: Are the operating budgets drawn up at the Tuungane School Complex managed in accordance with the budget lines provided for when they were drawn up?  Thus, to carry out this research successfully, we resorted to descriptive, comparative and systemic methods.  These were supported by documentary and free interview techniques for data collection as well as the statistical technique for processing these data. From the analysis of the results resulting from the processing of our data, we noted that the decision-makers of this school establishment did not respect the budget lines planned during the three years retained for our analyses, because the commitments of expenditure for certain headings n  were not executed as originally planned.  This is the case for the ''Personnel'' heading, because during these three years, it is observed that the employees do not benefit from the remuneration of their services for the last month of each school year.  The managers of this School Complex, justify this inconvenience by the insolvency of some students;  and yet other headings are not well served, even partially.